Learning grammar through singing? An intervention with EFL primary school learners. (February 2021) - Busse, Vera; Hennies, Chantal; Kreutz, Gunter; Roden, Ingo
Abstract: Singing has been advocated as an efficient supplementary strategy in language teaching, but little is known about its effect on grammar learning. We conducted an intervention study (five lessons) with primary EFL learners ( N = 57, mean age = 8.67, SD = 0.60) who were taught new vocabulary and grammar through either singing or speaking lyrics. The control group had new vocabulary introduced during regular lessons. Language gains were assessed through pre-, post-, and follow-up tests; affect was measured after each lesson. Students in the singing group showed similar vocabulary gains to students in the control group and larger gains than students in the speaking group. Importantly, singing students outperformed both groups on spelling and grammar learning. Positive affect was similar across intervention groups, but only the singing group showed significantly enhanced positive affect compared to the control group. Overall, results indicate a potential benefit of singing for grammar learning. Highlights: Singing can effectively support language learning processes. Singing students outperformed speaking students regarding vocabulary learning. Singing students outperformed speaking and control students on the grammar test. Progress on grammar learning was sustained over the retention interval. Singing students showed higher positive affect than control students.